A hybrid concentrated solar/biomass combustion system with internal thermal energy storage for fully dispatchable renewable electricity production in Mauritius. Issue 1 (11th May 2022) - Boretti, Alberto
Abstract: Wind and solar photovoltaic need expensive battery energy storage for dispatchability. Concentrated solar power plus internal thermal energy storage permits dispatchability, but it is convenient only in areas of large direct normal irradiance. A hybrid concentrated solar/combustion system is proposed for Mauritius, an area of modest direct normal irradiance, and biomass availability. The small, modular, 8 kW system for microgrid application comprises a beam down point concentrator, two tanks of molten salt thermal energy storage, a biomass combustion heater, a Stirling engine, and a generator. The hybrid system has a thermal energy supply solar of 41%, and a thermal energy supply by combustion fuel 59%. By assuming a zero CO2e emission for solar thermal energy supply (100% reduction of CO2e ) and a 21% CO2e emission for thermal energy from the combustion of bagasse (79% reduction) vs thermal energy from oil combustion, the proposed hybrid device would permit an 88% reduction of the emission of CO2 vs the reference oil combustion plant.